PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF DENGAN KONSEP TRI HITA KARANA UNTUK PEMBELAJARAN TEMATIK DI SD KELAS III GUGUS 6 KECAMATAN ABIANSEMAL, BADUNG, BALI - Winaya, I Made Astra; Okta Priantini, Dewa Ayu Made Manu; Widiastuti, Ni Luh Gede Karang (Widya Accarya, 2018)
AbstractThis study aims to develop interactive multimedia-based learning media with the concept of Tri Hita Karana. This learning media is intended for third grade elementary school students because the theme of learning is a lot to discuss human behavior in maintaining good relations with fellow humans, the environment and God. The purpose of this research is (1) to produce interactive learning media with the concept of Tri Hita Karana that is valid, practical, and effective, (2) to know the validity of interactive multimedia learning media with the Tri Hita Karana concept for elementary school students, (3) knowing the level of practicality of multimedia learning media with the Tri Hita Karana concept for elementary students, and (4) knowing the effectiveness of interactive multimedia learning media with the Tri Hita Karana concept in increasing students' learning motivation in the classroom. The type of research used, namely research and development (R & D) adopted from the Dick and Carey model. The design of this study was carried out in several stages, namely: (1) Determination of learning materials and basic competencies to be achieved by students. (2) needs analysis. (3) Development of learning media. (4) Trial of learning media. The population in this study were all third grade elementary school students in the cluster 6 area of Abiansemal District, Badung Regency consisting of 4 schools. The population in this study was 72 students. The technique of determining samples by means of random sampling with those chosen to be the primary school sample 1 Abiansemal 14 people and primary school 2 Abiansemal 10 people. Data was collected using observation, validation, questionnaire, and learning outcome tests. After the collected data were analyzed descriptively qualitative. As for the results of his research, namely: First, the results of the study of the validity of the learning media are in the valid category and feasible to use. Second, the results of the study showed that the learning media developed had fulfilled the practicality requirements, namely: 1) the implementation of the learning media, 2) the teacher's response to the learning media, and 3) the students' response to the learning media. Third, the results of the study showed the test scores of students' learning outcomes obtained an average of 76.73 and from 24 students reached completeness 95.83% when viewed from the value of the minimum completeness criteria used by the researcher, namely 72. The average motivation score was 3 , 78 in the very high category. Therefore, the learning media developed can be said to be effective. Fourth, there are several obstacles faced in implementing media learning both from the readiness of teachers and students, but can be overcome.Keywords: Learning Media, Interactive Multimedia, Tri Hita Karana, Motivation, Learning Outcomes.AbstrakPenelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis multimedia interaktif dengan konsep Tri Hita Karana. Media pembelajaran ini diperuntukan untuk siswa kelas III SD karena tema pembelajrannya banyak membahas perilaku manusia dalam menjaga hubungan baik dengan sesama manusia, lingkungan dan Tuhan. Tujuan dari penelitian ini adalah (1) untuk menghasilkan media pembelajaran interaktif dengan konsep Tri Hita Karana yang berkualitas valid, praktis, dan efektif, (2) mengetahui validitas media pembelajaran  multimedia interaktif dengan konsep Tri Hita Karana untuk siswa SD, (3) mengetahui tingkat kepraktisan media pembelajaran multimedia dengan konsep Tri Hita Karana untuk siswa SD, dan (4) mengetahui efektivitas media pembelajaran multimedia  interaktif dengan konsep Tri Hita Karana dalam meningkatkan motivasi belajar siswa di kelas. Jenis penelitian yang digunakan, yaitu penelitian dan pengembangan (R&D) mengadopsi dari model Dick and Carey. Rancangan  penelitian ini dilakukan dalam beberapa tahapan, yaitu: (1) Penetapan Materi pembelajaran dan kompetensi dasar yang akan dicapai siswa. (2) Analisis kebutuhan. (3) Pengembangan media pembelajaran. (4) Uji coba media pembelajaran. Populasi pada penelitian ini adalah seluruh siswa-siswi kelas III sekolah dasar yang ada di wilayah gugus 6 Kecamatan Abiansemal, Kabupaten Badung yang terdiri dari 4 sekolah. Jumlah populasi dalam penelitian ini adalah 72 orang siswa. Teknik penentuan sampel dengan cara random sampling dengan yang terpilih menjadi sampel SD 1 Abiansemal 14 orang dan SD 2 Abiansemal 10 orang. Data dikumpulkan menggunakan teknik observasi, validasi, kuesioner, dan tes hasil belajar. Setelah data terkumpul dianalisis secara deskriptif kualitatif. Adapun hasil penelitiannya, yaitu: Pertama, Hasil penelitian validitas media pembelajaran berada pada kategori valid dan layak digunakan. Kedua, hasil penelitian menunjukkan media pembelajaran yang dikembangkan telah memenuhi syarat kepraktisan, yaitu: 1) keterlaksanaan media pembelajaran, 2) respon guru terhadap media pembelajaran, dan 3) respon siswa terhadap media pembelajaran. Ketiga, hasil penelitian menunjukkan nilai tes hasil belajar siswa didapatkan rata-rata 76,73 dan dari 24 orang siswa mencapai ketuntasan 95,83% jika dilihat dari nilai KKM yang digunakan peneliti yaitu 72. Adapun nilai rata-rata motivasi diperoleh sebesar 3,78 dengan kategori sangat tinggi. Oleh karena itu, media pembelajaran yang dikembangkan dapat dikatakan efektif. Keempat, terdapat beberapa kendala-kendala yang dihadapi dalam mengimplemantasikan media pembelajran baik dari kesiapan guru dan siswa, namun telah dapat diatasi.Kata kunci:  Media Pembelajaran, Multimedia Interaktif, Tri Hita Karana, Motivasi, Hasil belajar.